Persepsi Konsumen Terhadap Atribut Komoditas Tomat Sayur - Aviola, Zulaika; Saidah, Zumi (Universitas Galuh, 2025)
One of the factors that drive the level of consumption of tomato vegetables is the needs, desires and perceptions of consumers. Purchasing decisions on a product can be influenced by a person's perception or attitude. Product attributes or product characteristics are an important thing to consider in analyzing a person's perception. The focus of this study is to determine consumer perceptions of vegetable tomato attributes. The number of samples taken in this study amounted to 100 respondents of the final consumers of the Caringin Main Market, Bandung City. This study uses descriptive analysis and mean score (spider web) to measure and determine consumer perceptions of vegetable tomato attributes. Based on the findings of this study, consumer perceptions of the attributes of color, size, taste, shape and freshness of respondents stated that there are three attributes that are most preferred and considered important in purchasing vegetable tomatoes, namely the attributes of color, size and freshness. While respondents consider the attributes of taste and shape as neutral attributes, meaning that these attributes are not the main factors considered by consumers in purchasing vegetable tomatoes.